Two Reasoning Strategies in Patients With Psychological Illnesses - Gangemi, Amelia; Tenore, Katia; Mancini, Francesco (Frontiers in Psychology, 2019)
Hyper-emotion theory states that psychological disorders are conditions in which individuals experience emotions that are appropriate to the situation but inappropriate in their intensity. When these individuals experience such an emotion, they are inevitably compelled to reason about its cause. They therefore develop characteristic strategies of reasoning depending on the particular hyper-emotion they experience. In anxiety disorders (e.g., panic attack, social phobia), the perception of a disorder-related threat leads to hyper-anxiety; here, individuals’ reasoning is corroboratory, adducing evidence that confirms the risk (corroboratory strategy). In obsessive-compulsive disorders, the threat of having acted in an irresponsible way leads to both hyper-anxiety and guilt; here, individuals’ reasoning is refutatory, adducing only evidence disconfirming the risk of being guilty (refutatory strategy). We report three empirical studies corroborating these hypotheses. They demonstrate that patients themselves recognize the two strategies and spontaneously use them in therapeutic sessions and in evaluating scenarios in an experiment.